The Nature, Value, and Experience of Engagement in Pediatric Rehabilitation: Perspectives of Youth, Caregivers, and Service Providers. (2nd January 2020) - King, Gillian; Chiarello, Lisa A.; Ideishi, Roger; D'Arrigo, Rachel; Smart, Eric; Ziviani, Jenny; Pinto, Madhu
ABSTRACT: Purpose : To conduct a qualitative investigation of engagement in pediatric rehabilitation therapy. Methods : Interviews were conducted with 10 youth, 10 caregivers, and 10 service providers. Transcripts were analyzed thematically using an inductive approach. Results : Themes illustrated three perspectives: engagement as a connection with components of the therapy process, engagement as working together, and engagement as an affective and motivational process. Engagement created valued connections with therapy components and forward momentum for therapy. Conclusions : The themes supported a view of engagement as complex, transactional, and multidimensional. Participants focused on different, yet not discrepant, aspects of engagement. Youth focused on having fun and personal connection with service providers. Caregivers provided a more complex perspective encompassing both their own and their child's engagement, with an emphasis on relationship, understanding what is taking place, and feeling valued in the process. Service providers highlighted goal attainment and the value of engagement in bringing about outcomes.